Pengintegrasian Al-Islam Kemuhammadiyahan dalam Pembelajaran Membaca untuk Mahasiswa PGSD - Aprizan; Refril Dani (LPPM Universitas Muhammadiyah Muara Bungo, 2026)
Reading instruction is not only aimed at improving students’ text comprehension, but can also be used to instill Islamic values. This study aimed to describe the implementation, strategies, methods, and obstacles in integrating Al-Islam and Kemuhammadiyahan (AIK) into reading instruction. The study employed a descriptive qualitative approach. The informants consisted of 10 participants: 1 lecturer and 9 students of the Primary School Teacher Education Program at Muhammadiyah University of Muara Bungo. Data were collected through observation, interviews, and documentation, then analyzed using the Miles and Huberman model: data reduction, data display, and verification. The findings revealed that reading instruction was conducted in three stages: preliminary, core, and closing activities. AIK integration strategies included selecting reading materials containing Islamic values, relating text content to Islamic teachings, and reflecting on moral messages in the texts. The lecturer applied various methods, such as discussion, reading comprehension, question-and-answer, assignments, role modeling, and connecting the text content to students’ daily lives. The main obstacles were limited reading materials, limited instructional time, and differences in students’ understanding of Islamic values. It can be concluded that integrating AIK into reading instruction improves text comprehension while simultaneously serving as a medium for instilling Islamic values in students.